Impact of different urinary tract infection phenotypes within the first year post‐transplant on renal allograft outcomes. Issue 7 (26th March 2022) - Brune, Jakob E.; Dickenmann, Michael; Wehmeier, Caroline; Sidler, Daniel; Walti, Laura; Golshayan, Dela; Manuel, Oriol; Hadaya, Karine; Neofytos, Dionysios; Schnyder, Aurelia; Boggian, Katia; Müller, Thomas; et al.
Abstract : In this study, we investigated the clinical impact of different urinary tract infection (UTI) phenotypes occurring within the first year after renal transplantation. The population included 2368 transplantations having 2363 UTI events. Patients were categorized into four groups based on their compiled UTI events observed within the first year after transplantation: (i) no colonization or UTI ( n  = 1404; 59%), (ii) colonization only ( n  = 353; 15%), (iii) occasional UTI with 1–2 episodes ( n  = 456; 19%), and (iv) recurrent UTI with ≥3 episodes ( n  = 155; 7%). One‐year mortality and graft loss rate were not different among the four groups, but patients with recurrent UTI had a 7‐10 ml/min lower eGFR at year one (44 ml/min vs. 54, 53, and 51 ml/min; p  < .001). UTI phenotypes had no impact on long‐term patient survival ( p  = .33). However, patients with recurrent UTI demonstrated a 10% lower long‐term death‐censored allograft survival ( p  < .001). Furthermore, recurrent UTI was a strong and independent risk factor for reduced death‐censored allograft survival in a multivariable analysis (HR 4.41, 95% CI 2.53–7.68, p  < .001). We conclude that colonization and occasional UTI have no impact on pertinent outcomes, but recurrent UTI are associated with lower one‐year eGFR and lower long‐term death‐censored allograft survival. Better strategies to prevent and treat recurrent UTI are needed. Abstract : Recurrent but not occasional urinary tract infections are associated with a lower one‐year eGFR and lower long‐term death‐censored allograft survival.